PENINGKATAN PENDAPATAN ASLI DAERAH MELALUI PENGELOLAAN KAWASAN STRATEGIS PARIWISATA DI KOTA BENGKULU: Increasing Local Own-Source Revenue Through The Management Of Strategic Tourism Areas In Bengkulu City - Sahala Deo Sambegana Aritonang; Ninuk Wijiningsih (Reformasi Hukum Trisakti, 2026)
As the Provincial capital, Bengkulu city possesses significant tourism potential across natural, cultural and historical sectors. This strategic asset, if managed effectively, could drive economic growth and serve as primary source of local genuine revenue (PAD). Despite iconic landmarks such as “pantai panjang” and “fort Marlborough”, the tourism sector’s contribution to Bengkulu city’s PAD remains disproportionately low relative to its potential. Financial data for 2024 shows PAD realization at only IDR 184.17 billion, falling significantly short of the IDR 320 billion target set in the regional budget (APBD). Consequently, regional financial management in the tourism sector must prioritize the principles of legality, effectiveness, efficiency and compliance with prevailing regulations. This research addresses the legal issue of local government efforts to increase PAD through strategic tourism areas in Bengkulu city. This research using a normative juridical method, this descriptive study utilizes secondary data supported by primary data, analyzed qualitatively through deductive reasoning. The research concludes that the government’s financial management remains suboptimal in achieving the predetermined targets estabilished in the Bengkulu city APBD